Changes in extracellular matrix in subcutaneous small resistance arteries of patients with essential hypertension. (4th July 2018) - Favero, Gaia; Paini, Anna; De Ciuceis, Carolina; Rodella, Luigi F.; Moretti, Enrico; Porteri, Enzo; Rossini, Claudia; Ministrini, Silvia; Solaini, Leonardo; Stefano, Caletti; Coschignano, Maria Antonietta; Brami, Valeria; et al.
Abstract: Background: In the development of hypertensive microvascular remodeling, a relevant role may be played by changes in extracellular matrix proteins. Aim of this study was the to evaluate some extracellular matrix components within the tunica media of subcutaneous small arteries in 9 normotensive subjects and 12 essential hypertensive patients, submitted to a biopsy of subcutaneous fat from the gluteal or the anterior abdominal region. Patients and Methods: Subcutaneous small resistance arteries were dissected and mounted on an isometric myograph, and the tunica media to internal lumen ratio was measured. In addition, fibronectin, laminin, transforming growth factor-beta-1 (TGF-β1) and emilin-1 contents within the tunica media were evaluated by immunofluorescence and relative immunomorphometrical analysis (immunopositivity % of area). The total collagen content and collagen subtypes within the tunica media were evaluated using both Sirius red staining (under polarized light) and immunofluorescence assay. Results: Normotensive controls had less total and type III collagen in respect with hypertensive patients. Fibronectin and TGF-β1 tunica media content was significantly greater in essential hypertensive patients, compared with normotensive controls, while laminin and emilin-1 tunica media content was lesser in essential hypertensive patients, compared with normotensive controls. A significant correlation was observed between fibronectin tunica media content and media to lumen ratio. Conclusions: Our results indicate that, in small resistance arteries of patients with essential hypertension, a relevant fibrosis may be detected; fibronectin and TGF-β1 tunica media content is increased, while laminin and emilin-1 content is decreased; these changes might be involved in the development of small resistance artery remodeling in humans.